Inverted U-shaped association between the systemic immune-inflammation index and colorectal polyps in Chinese patients: a cross-sectional study - Jie Bao; Yajie Teng; Yingxue Yang; Qinghua Wang (Frontiers in Medicine)
PurposeThe systemic immune-inflammation index (SII) has been found to be associated with various inflammatory and neoplastic diseases. The aim of this study was to investigate the relationship between the SII and colorectal polyps (CPs) in Chinese patients.MethodsThis was a cross-sectional study. We retrospectively collected data from 3,028 Chinese patients who underwent physical examinations, including colonoscopy, from 2018 to 2022. We conducted a comparative analysis of patient characteristics among those with adenomatous polyps, non-adenomatous polyps, and individuals without CPs using descriptive statistics. We calculated the SII for each group and assessed the relationship between SII values and the presence of CPs.ResultsOur study included 3,028 individuals, of whom 1,432 (47.29%) had colorectal polyps. After adjusting for confounding variables, the natural logarithm of the SII (Ln-SII) was significantly associated with the prevalence of adenomatous polyps in both males and females, with an odds ratio (OR) of 0.76 [95% confidence interval (CI): 0.65–0.88, p = 0.0003]. An inverted U-shaped relationship was observed between Ln-SII and the prevalence of colorectal polyps, including both adenomatous and non-adenomatous polyps, with a cut-off point at 5.78 (5.39 for adenomatous polyps and 5.79 for non-adenomatous polyps). Below this cut-off point, a significant association with colorectal polyps was identified, with an OR of 1.73 (95% CI: 1.25–2.40, p = 0.0009). Specifically, for adenomatous polyps, the OR was 2.91 (95% CI: 1.03–8.20, p = 0.0437), and for non-adenomatous polyps, the OR was 1.86 (95% CI: 1.31–2.65, p = 0.0006). Beyond the cut-off point, the association between Ln-SII and colorectal polyps remained significant, with an OR of 0.56 (95% CI: 0.46–0.68, p < 0.0001). In the adenomatous polyps group, the OR was 0.57 (95% CI: 0.43–0.74, p < 0.0001), and in the non-adenomatous polyps group, the OR was 0.57 (95% CI: 0.46–0.70, p < 0.0001).ConclusionThe inverted U-shaped association between Ln-SII and the risk of colorectal polyps highlights the potential relevance of monitoring variations in SII and suggests that SII may be a promising predictor for colorectal polyp development.